Electrical Stimulation of pediatric cardiac‐derived c‐kit+ progenitor cells improves retention and cardiac function in right ventricular heart failure. (22nd October 2019) - Maxwell, Joshua T.; Trac, David; Shen, Ming; Brown, Milton E.; Davis, Michael E.; Chao, Myra S.; Supapannachart, Krittin J.; Zaladonis, Carly A.; Baker, Emily; Li, Martin L.; Zhao, Jennifer; Jacobs, Daniel I.
Abstract: Nearly 1 in every 120 children born has a congenital heart defect. Although surgical therapy has improved survival, many of these children go on to develop right ventricular heart failure (RVHF). The emergence of cardiovascular regenerative medicine as a potential therapeutic strategy for pediatric HF has provided new avenues for treatment with a focus on repairing or regenerating the diseased myocardium to restore cardiac function. Although primarily tried using adult cells and adult disease models, stem cell therapy is relatively untested in the pediatric population. Here, we investigate the ability of electrical stimulation (ES) to enhance the retention and therapeutic function of pediatric cardiac‐derived c‐kit + progenitor cells (CPCs) in an animal model of RVHF. Human CPCs isolated from pediatric patients were exposed to chronic ES and implanted into the RV myocardium of rats. Cardiac function and cellular retention analysis showed electrically stimulated CPCs (ES‐CPCs) were retained in the heart at a significantly higher level and longer time than control CPCs and also significantly improved right ventricular functional parameters. ES also induced upregulation of extracellular matrix and adhesion genes and increased in vitro survival and adhesion of cells. Specifically, upregulation of β1 and β5 integrins contributed to the increased retention of ES‐CPCs. Lastly, we show that ES induces CPCs to release higher levels of pro‐reparative factors in vitro. These findings suggest that ES can be used to increase the retention, survival, and therapeutic effect of human c‐kit + progenitor cells and can have implications on a variety of cell‐based therapies. Stem Cells 2019;37:1528–1541 Abstract : Top, Conceptual diagram of ex vivo modification of cells. Cells are isolated, modified, and administered to patients as autologous or allogeneic therapies. Bottom, ex vivo modification of pediatric cardiac‐derived progenitor cells with electrical stimulation promotes retention of cells and improves cardiac function in a rat model of heart failure.